CONCEPTUAL PRINCIPLES OF USING THE TECHNOLOGICAL APPROACH IN THE EDUCATIONAL PROCESS - Podberezsky, M.K. (Pedagogy of Higher and Secondary Education, 2022)
The article is devoted determination of conceptual bases of taking technological ap proach to organization of educational process. The features of application of educational technologies are certain by comparison to the process of production.